PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN MENGGUNAKAN MEDIA GAMBAR TERHADAP KETERAMPILAN MENULIS PUISI PADA SISWA KELAS IV SD INPRES PARE’-PARE’ KEC. BAJENG KAB. GOWA - Indah Nur Fadhilah; Tasrif Akib; Abd.Rajab (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
One of the important language skills to develop in elementary school is poetry writing, which can foster students' sensitivity, imagination, and creative thinking. Therefore, an innovative learning model is needed that incorporates media such as discovery learning. This research is a quantitative, quasi-experimental study using a one-group pretest-posttest design, involving one group of subjects who are given treatment after a pretest and then concluded with a posttest. The study was conducted in the fourth grade of SD Inpres Pare'-Pare', Bajeng District, Gowa Regency, with a sample size of 24 students. The research instruments consisted of a poetry writing skills test and a student activity observation sheet. The results showed an average pre-test score of 47.71 and a post-test score of 88.13. The t-test count was 20.74, and the t-table value at a 5% significance level was 2.069. Therefore, the use of the discovery learning model with images as a medium influenced the improvement of students' poetry writing skills. Keywords: Discovery Learning, image media, writing poetry